Um estudo sobre o movimento lógico-histórico do conceito de continuidade - Silva, Rafael Siqueira (2019)
The aim of this paper is to investigate the logical-historical movement of the concept of Continuity through a historical-epistemological analysis, with a view to determining the essential relations that can be configured as conceptual nexus. Assuming the theoretical contributions of the Historical-Cultural theory, the conceptual nexus are understood as the synthesis of the internal and external relations of a concept, whose determination is realized through the logical-historical movement. Thus, it is established as a guiding question: What are the relations established in the logical-historical movement of the concept of Continuity that can be configured as conceptual nexus from the realization of a historical-epistemological analysis? The research methodology is based on the principles of historical-dialectical materialism and is constituted by the realization of the State of the Art of research on Continuity teaching and the historical-epistemological analysis of historiographical sources that address essential aspects on the development of this concept. The results point to the determination of conceptual connections in the commensurable-incommensurable, discrete-continuous, infinite-infinitesimal, permanence-fluency, punctual-general and rigor-intuition dialectical pairs. Reflections on the results indicate the resignification of the curriculum structure of Continuity in the fields of basic and higher education. In addition, it also discusses the need for the realization of teaching organization of Continuity based on conceptual nexus and conceptual appropriation by students.